Process for identifying meso-disruption of granite mineral components
Through the comprehensive application of polarization microscope, scanning electron microscope and energy spectrometer, combined with a variety of observation methods, the detailed damage of granite mineral components is identified, which solves the problem of difficult to analyze granite mesoscopic damage in the existing technology, and achieves a more complete granite Destructive feature description and reliability of test results.
Patent Information
- Application Number
- CN202411465841.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-17
AI Technical Summary
The prior art is difficult to effectively reveal the nature of granite damage from the perspective of sub-destruction of granite mineral components, and lacks systematic methods to analyze the relationship between mineral components, mesostructure and mechanical parameters, affecting the safety and economy of underground engineering.
Using a comprehensive application of polarization microscope, scanning electron microscope and energy spectrometer, the preparation of mineral flakes and cross-section samples is carried out, and a variety of observation methods are combined to conduct qualitative and quantitative analysis of mineral components and mesoscopic destruction methods, including polarization microscope determining mineral components and scanning electron microscope observation Cross-sectional morphology, energy spectrometer analyzes element distribution, and realizes a comprehensive judgment of mineral composition and mesoscopic damage methods.
Improve the analysis accuracy and depth of granite mesoscopic damage characteristics, provide systematic testing methods, ensure the repeatability and reliability of test results, apply to different laboratory conditions, fill in the identification of mineral components mesoscopic damage methods The gap provides a new direction for the rock damage mechanism.
Smart Images

Figure CN119322025A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rock mineral component identification and determination, in particular to a process for identifying the microscopic destruction of granite mineral components. Background Art
[0002] my country has abundant granite species and a wide distribution, with an exposed area of 860,000 km 2 , accounting for about 9% of the country's land area. In the southwest of my country, due to the influence of plate subduction and collision, granite is mostly exposed along the junction area between rigid blocks, distributed in a belt, and has a brittle foundation for rock burst damage. Nowadays, more and more underground projects appear in the deep mountain canyon areas in the west of China where dynamic geological effects are strong. The occurrence of deep granite geological disasters has a huge impact on personal safety and economic conditions during underground engineering excavation. Therefore, it is very important to explore the mechanism of granite destruction. Nowadays, indoor tests are mainly carried out, which can be divided into macro tests and micro observations. In macro tests, uniaxial compression tests, conventional triaxial tests and true triaxial tests are mainly used to assist other observation methods such as acoustic emission to explore the stress-strain curve, strength deformation characteristics and macro failure characteristics of granite. Researchers have done a lot of work in this regard and are becoming more and more perfect. However, in terms of micro failure modes, only a single micro observation method, such as scanning electron microscopy, CT, energy spectrometer, X-ray and polarizing microscope observation and analysis of mineral composition and content or a single scanning electron microscope photograph, has been used. It has not been possible to effectively reveal the essence of granite failure from the perspective of micro failure of the mineral composition of granite. Since the rock itself is a collection of multiple mineral components, exploring the micro failure mode of granite under the mineral composition from the scale of mineral composition can provide a deeper interpretation of the macro failure mode of granite.
[0003] From a microscopic perspective, rocks are heterogeneous, anisotropic natural materials composed of a variety of minerals. The differences in rock mineral types, cementation methods of mineral particles, and micromechanical parameters lead to different elastic moduli and strength characteristics of various rocks. How to analyze the relationship between mineral composition, microstructure, mineral mechanical parameters and rock macroscopic parameters, and explain the microscopic geomechanical mechanism of rock macroscopic mechanical behavior, has always been a research hotspot for academic and engineering circles at home and abroad. Summary of the invention
[0004] The purpose of the present invention is to provide a process for identifying the microscopic damage of granite mineral components to solve the shortcomings of the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A process for identifying mesoscopic damage to granite mineral components, comprising the following steps:
[0007] S1: Process the unweathered granite obtained from the site into mineral slices, observe them using a polarizing microscope, determine the mineral composition of the rock, and determine the types of elements contained in it;
[0008] S2: Prepare the granite sample whose fractured section needs to be observed after field destruction or indoor test destruction, observe it with a scanning electron microscope, determine the specific fractured morphology of the granite rock, and identify the mesoscopic destruction mode of the fixed point area;
[0009] S3: In a specific morphological area of the above sample, the element distribution of the area is obtained by point scanning and surface scanning using an energy spectrometer;
[0010] S4: Compare the element distribution of a specific area obtained in S3 with the element distribution of different mineral components obtained in S1 to determine the mineral composition of the area;
[0011] S5: Combine S4 with S2 and use scanning electron microscopy to determine the microscopic destruction mode of the mineral components in the rock.
[0012] Furthermore, the specific method for making the mineral slice in S1 is as follows:
[0013] S101: Cutting: First select the fresh and unweathered part of the rock, and then use a diamond saw to cut it into the appropriate size for the glass slide;
[0014] S102: Grinding: Grind the cut rock specimen and the glass slide to be glued with #600-#1000 silicon carbide powder respectively to make the cut surface of the rock specimen smooth;
[0015] S103: Gluing: The processed rock sample is glued to the frosted glass with epoxy resin. The contact surface is cleaned with alcohol before gluing. After gluing, it is placed on a fixed platform and baked at a low temperature of 50°C for 6 to 8 hours.
[0016] S104: Sectioning: After the glue hardens, the specimen is placed on a thin slice cutting machine and cut and ground into a thickness of 100 to 150 μm;
[0017] S105: Grinding: The thickness of the specimen is determined by a micrometer, and then the 100-150μm thick rock specimen is fixed on a vacuum chuck using the vacuum principle, and then directly ground on a thin-section grinding disc to a standard thickness of 30μm;
[0018] S106: Polishing: Polish the thin sheets with 0.3-0.05 μm aluminum powder polishing liquid.
[0019] Furthermore, the types of rock mineral components identified in S1 include:
[0020] Quartz minerals contain Si and O elements;
[0021] Potassium feldspar minerals contain a specific element, K;
[0022] Plagioclase contains a specific element, Na;
[0023] Mica contains specific elements Mg and Fe.
[0024] Furthermore, the sample preparation method of the granite SEM sample in S2 is as follows:
[0025] S201: Grinding: Take out the granite sample obtained by destruction into a size of 1cm*1cm*0.2cm square, use sandpaper to grind the reverse side of the observed failure section flat, and mark the grinded surface;
[0026] S202: Drying: Dry the polished sample in a muffle furnace for 12 hours;
[0027] S203: Gold spraying: Use an ion sputtering device to spray gold on the sample.
[0028] Furthermore, the specific cross-sectional morphologies in S2 include honeycomb, step, slip, herringbone and flat shapes, among which the honeycomb shape is a typical intergranular failure with a rough fracture, while the step, slip, herringbone and flat shapes are all transgranular failures with a smooth fracture.
[0029] Furthermore, in S3, at least three points are selected for point scanning in a specific morphological area to obtain qualitative and quantitative analysis of the elements of the three points.
[0030] Furthermore, the elements distributed in S4 are as follows: quartz contains only Si and O elements, potassium feldspar contains K but not Na or a small amount of Na, plagioclase contains Na but not K or a small amount of K, and mica contains more Mg and Fe elements.
[0031] Furthermore, in S5, at least 10 cross-sectional morphology samples of each mineral component are determined.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The process for identifying the mesoscopic damage of granite mineral components of the present invention provides a comprehensive analysis from mineral components to mesoscopic damage modes through the comprehensive application of multiple observation methods, combining polarizing microscopes, scanning electron microscopes and energy spectrometers, and realizes the comprehensive judgment of the qualitative and quantitative analysis of mineral components and the mesoscopic damage modes, providing a more complete description of the mesoscopic damage characteristics of granite, and improving the accuracy and depth of the analysis.
[0034] 2. The process for identifying the microscopic destruction of granite mineral components of the present invention provides a systematic test method, including sample preparation, observation and analysis, and data comparison, and a standardized operating procedure, which ensures the repeatability and reliability of the test results. The method is simple and easy to use and is suitable for test operations under different laboratory conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a process flow chart of an embodiment of the present invention;
[0036] Figure 2 A physical image of a specific cross-sectional morphology determined by a scanning electron microscope of the present invention;
[0037] Figure 3 It is a point scan diagram of the energy spectrometer of the present invention;
[0038] Figure 4 For the present invention Figure 3 Midpoint Sweep Figure 1 Element content distribution diagram of
[0039] Figure 5 This is a statistical diagram of the microscopic destruction modes of different mineral components of granite according to the present invention. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] See also Figure 1 For granite samples that have been damaged on site or in indoor tests, the present invention provides a process for identifying the microscopic damage of granite mineral components using a polarizing microscope, a scanning electron microscope, and an energy spectrometer, which mainly includes the following steps:
[0042] S1: The unweathered granite obtained from the site is processed into mineral slices, which are observed using a polarizing microscope to determine the type of mineral composition of the rock and the type of elements contained therein; the specific method for making the mineral slices is as follows:
[0043] S101: Cutting: First select the fresh and unweathered part of the rock, and then use a diamond saw to cut it into the appropriate size for the glass slide;
[0044] S102: Grinding: Grind the cut rock specimen and the glass slide to be glued with #600-#1000 silicon carbide powder respectively to make the cut surface of the rock specimen smooth;
[0045] S103: Gluing: The processed rock sample is glued to the frosted glass with epoxy resin. The contact surface is cleaned with alcohol before gluing. After gluing, it is placed on a fixed platform and baked at a low temperature of 50°C for 6 to 8 hours.
[0046] S104: Sectioning: After the glue hardens, the specimen is placed on a thin slice cutting machine and cut and ground into a thickness of 100 to 150 μm;
[0047] S105: Grinding: The thickness of the specimen is determined by a micrometer, and then the 100-150μm thick rock specimen is fixed on a vacuum chuck using the vacuum principle, and then directly ground on a thin-section grinding disc to a standard thickness of 30μm;
[0048] S106: Polishing: Polish the thin slices with 0.3-0.05 μm aluminum powder polishing liquid;
[0049] The types of rock mineral components determined by the above steps include:
[0050] Quartz minerals contain Si and O elements;
[0051] Potassium feldspar minerals contain a specific element, K;
[0052] Plagioclase contains a specific element, Na;
[0053] Mica contains specific elements Mg and Fe.
[0054] S2: Prepare a sample of the granite sample that needs to be observed after field destruction or indoor test destruction, and observe it using a scanning electron microscope to determine the specific cross-sectional morphology of the granite rock and identify the microscopic destruction mode of the fixed point area; the method for preparing the granite scanning electron microscope sample is as follows:
[0055] S201: Grinding: Take out the granite sample obtained by destruction into a size of 1cm*1cm*0.2cm square, use sandpaper to grind the reverse side of the observed failure section flat, and mark the grinded surface;
[0056] S202: Drying: Dry the polished sample in a muffle furnace for 12 hours;
[0057] S203: Gold spraying: Use an ion sputtering device to spray gold on the sample;
[0058] The specific cross-sectional morphologies in this step include honeycomb, step, slip, herringbone and flat shapes. Among them, the honeycomb shape is a typical intergranular failure with a rough fracture, while the step, slip, herringbone and flat shapes are all transgranular failures with a smooth fracture.
[0059] S3: In a specific morphological area of the above sample, the element distribution of the area is obtained by point scanning and surface scanning using an energy spectrometer; wherein, the point scanning method of the specific morphological area is to take at least 3 points for point scanning to obtain the qualitative and quantitative analysis of the elements of the three points.
[0060] S4: Compare the element distribution of the specific area obtained in S3 with the element distribution of different mineral components obtained in S1 to determine the mineral composition of the area; wherein, the elements for distribution comparison are: quartz contains only Si and O elements, potassium feldspar contains K element but no Na element or a small amount of Na element, plagioclase contains Na element but no K element or a small amount of K element, and mica contains more Mg and Fe elements.
[0061] S5: Combine S4 with S2 and determine the microscopic destruction mode of the mineral components in the rock through a scanning electron microscope, wherein at least 10 cross-sectional morphology samples of each mineral component are determined.
[0062] like Figure 2-5 To further better explain the embodiments of the present invention, the present invention is further described below with reference to a specific example:
[0063] In order to obtain the destruction mode of granite mineral components in an underground project, granite rocks taken from a project site were cut, flattened, glued, sliced, ground and polished into mineral slices, and the mineral slices were quantitatively and qualitatively analyzed using a polarizing microscope:
[0064] Table 1 Main mineral components and representative elements of the granite
[0065] Mineral Name content(%) Particle size / mm Element Category form Quartz (Qtz) 40 0.15–3.00 Si、O granular Potassium feldspar(Kfs) 13 0.30–5.70 K. Al Lath-shaped, granular Plagioclase(PI) 35 0.20–3.00 Na、Al Lath Mica(Bt) 12 0.20–1.60 Mg, Fe Flake
[0066] At this time, it was determined that different mineral components in granite contain specific element contents. Quartz minerals contain only Si and O elements, potassium feldspar minerals contain the specific element K, plagioclase contains the specific element Na, and mica contains the specific elements Mg and Fe.
[0067] Then, the granite rock samples were processed into scanning electron microscope samples through grinding, drying and gold spraying processes. The samples were observed using a scanning electron microscope to determine the specific cross-sectional morphology, among which the specific cross-sectional morphologies included honeycomb, step, slip, herringbone and flat shapes. The cross-sectional morphology can reflect the specific mesoscopic failure mode, among which the honeycomb shape is a typical intergranular failure with a rough fracture, while others such as step, slip, herringbone and flat shapes are transgranular failures with a smooth fracture.
[0068] The specific cross-sectional morphology position is then observed using an energy spectrometer. The elemental composition obtained by point scanning and surface scanning corresponds to the specific elements of different mineral components obtained by a polarizing microscope, so that the type of mineral component with a specific morphology in the area can be determined, taking mica as an example.
[0069] After obtaining that the mineral composition of the cross-sectional morphology area is mica, combined with the destruction mode of the cross-sectional morphology, the cross-sectional morphology of this area is step-shaped, so it is a transgranular fracture.
[0070] By identifying 148 specific cross-sectional morphologies of rock samples obtained from the on-site sampling, it was found that 22 quartz samples, 68 plagioclase samples, 13 potassium feldspar samples and 45 mica samples were identified; among the 22 quartz samples, 12 had honeycomb cross-sectional morphologies and 10 had step-shaped cross-sectional morphologies, so the probability of quartz undergoing intergranular and transgranular fractures was basically the same; among the 19 potassium feldspar samples, 6 had honeycomb cross-sectional morphologies and 7 had step-shaped and wavy cross-sectional morphologies, so the probability of potassium feldspar undergoing intergranular and transgranular fractures was basically the same; among the 68 plagioclase samples, 10 had honeycomb cross-sectional morphologies and 58 had step-shaped, fishbone-shaped and flat cross-sectional morphologies, so plagioclase was more likely to undergo transgranular fractures; among the 45 mica samples, the cross-sectional morphologies were almost all scratch clusters and lamellar, indicating that mica was most likely to undergo transgranular fractures.
[0071] In summary: the process for identifying the mesoscopic destruction of granite mineral components provided by the present invention is realized based on a variety of mesoscopic observation equipment, including a polarizing microscope, a scanning electron microscope and an energy spectrometer, and the order of use is polarizing microscope-scanning electron microscope-energy spectrometer. The elemental composition of the mineral components is determined by the polarizing microscope, the cross-sectional morphology, that is, the mesoscopic destruction mode of the area is determined by the scanning electron microscope, and the energy spectrometer determines the mineral components of the specific area. Therefore, the whole process determines the mesoscopic destruction mode of the mineral components. The present invention utilizes a variety of mesoscopic equipment and gradually observes and determines the experimental method, which not only fills the gap in the identification of the mesoscopic destruction mode of the mineral components, but also provides a new direction for exploring the rock destruction mode.
[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for identifying mesoscopic damage of granite mineral components, characterized in that: The following steps are involved: S1: Process the unweathered granite obtained from the site into mineral slices, observe them using a polarizing microscope, determine the mineral composition of the rock, and determine the types of elements contained in it; S2: Prepare the granite sample whose fractured section needs to be observed after field destruction or indoor test destruction, observe it with a scanning electron microscope, determine the specific fractured morphology of the granite rock, and identify the mesoscopic destruction mode of the fixed point area; S3: In a specific morphological area of the above sample, the element distribution of the area is obtained by point scanning and surface scanning using an energy spectrometer; S4: Compare the element distribution of a specific area obtained in S3 with the element distribution of different mineral components obtained in S1 to determine the mineral composition of the area; S5: Combine S4 with S2 and use scanning electron microscopy to determine the microscopic destruction mode of the mineral components in the rock.
2. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: The specific method for making the mineral slices in S1 is as follows: S101: Cutting: First select the fresh and unweathered part of the rock, and then use a diamond saw to cut it into the appropriate size for the glass slide; S102: Grinding: Grind the cut rock specimen and the glass slide to be glued with #600-#1000 silicon carbide powder respectively to make the cut surface of the rock specimen smooth; S103: Gluing: The processed rock sample is glued to the frosted glass with epoxy resin. The contact surface is cleaned with alcohol before gluing. After gluing, it is placed on a fixed platform and baked at a low temperature of 50°C for 6 to 8 hours. S104: Sectioning: After the glue hardens, the specimen is placed on a thin slice cutting machine and cut and ground into a thickness of 100 to 150 μm; S105: Grinding: The thickness of the specimen is determined by a micrometer, and the 100-150 μm thick rock specimen is fixed on a vacuum chuck using the vacuum principle, and then directly ground on a thin-section grinding disc to a standard thickness of 30 μm; S106: Polishing: Polish the thin sheets with 0.3-0.05 μm aluminum powder polishing liquid.
3. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: The types of rock mineral components identified in S1 include: Quartz minerals contain Si and O elements; Potassium feldspar minerals contain a specific element, K; Plagioclase contains a specific element, Na; Mica contains specific elements Mg and Fe.
4. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: The sample preparation method of the granite SEM sample in S2 is as follows: S201: Grinding: Take out the granite sample obtained by destruction into a size of 1cm*1cm*0.2cm square, use sandpaper to grind the reverse side of the observed failure section flat, and mark the grinded surface; S202: Drying: Dry the polished sample in a muffle furnace for 12 hours; S203: Gold spraying: Use an ion sputtering device to spray gold on the sample.
5. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: The specific cross-sectional morphologies in S2 include honeycomb, step, slip, herringbone and flat shapes. Among them, the honeycomb shape is a typical intergranular failure with a rough fracture surface, while the step, slip, herringbone and flat shapes are all transgranular failures with a smooth fracture surface.
6. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: In S3, at least three points are scanned in a specific morphological area to obtain qualitative and quantitative analysis of the elements at these three points.
7. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: The elements distributed in S4 are as follows: quartz contains only Si and O, potassium feldspar contains K but no Na or a small amount of Na, plagioclase contains Na but no K or a small amount of K, and mica contains more Mg and Fe.
8. A process for identifying mesoscopic damage of granite mineral components as claimed in claim 1, characterized in that: In S5, at least 10 cross-sectional morphology samples are required to determine each mineral component.